SSR markers linked to stem canker resistance in soybean Glycine max - Gilli, Javier Ramon; Vellicce, Gabriel Ricardo; Bernardi, Clarisa Noelia (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2020)
In this work, we studied 40 samples of Diaporthe phaseolorum var. meridionalis (Dpm), causal agent of stem canker in soybeans (SCS). In the susceptible genotype Golondrina65 the isolate RSF12 showed the highest percentage of the dead plant index (DP = 85.7 %) and was used to characterize all known sources of resistance to Dpm. The soybean MJ19RR experimental line showed the best behaviour against this isolate with a DP = 2.4 % and was used to develop a segregating population with the suscep¬tible cultivar FT-2001. In the F2 generation, the chi-square test determined a 3:1 ratio of resistant plants against susceptible plants, as expected for a dominant gene. In order to advance in our study we propose, as objective, to locate in the soybean genetic map the resistance to Diaporthe phaseolorum var. meridionalis. The Bulked Segregant Analyses and the genetic linkage study identified a region of chromosome 6 of the genetic map of soybean, located at 13.3 cM from the Satt433 locus associated with resistance to SCS. The soybean experimental line MJ19RR was selected as the best source of resistance, and it is available in the active bank of soybean germplasm of INTA, for the genetic control of this disease. The results obtained in this work represent a first approximation for the understanding of the genetic basis of resistance to SCS.